Application of Cycloaddition Reactions to the Syntheses of Novel Boron Compounds - John A. Maguire; Narayan S. Hosmane; Yinghuai Zhu; Xiao Siwei (Molecules, 2010)
This review covers the application of cycloaddition reactions in forming the boron-containing compounds such as symmetric star-shaped boron-enriched dendritic molecules, nano-structured boron materials and aromatic boronic esters. The resulting boron compounds are potentially important reagents for both materials science and medical applications such as in boron neutron capture therapy (BNCT) in cancer treatment and as drug delivery agents and synthetic intermediates for carbon-carbon cross-coupling reactions. In addition, the use of boron cage compounds in a number of cycloaddition reactions to synthesize unique aromatic species will be reviewed briefly.